Prevalence of suicidal thoughts and behaviors and its association with body dissatisfaction in adolescents Prevalência de pensamentos e comportamentos suicidas e associação com a insatisfação corporal em adolescentes - Claumann G.S.* (2018)
© 2018, Editora Cientifica Nacional Ltda. All rights reserved.Objective: To estimate the prevalence of suicidal thoughts and behaviors and its association with body image dissatisfaction in adolescents. Methods: Participants were 1,090 adolescents (501 male and 589 female), with mean age of 16.2 (1.1) years, who were high school students in Sao Jose-SC. In a self-administered questionnaire, adolescents answered sociodemographic questions (sex, age), sexual maturation, body dissatisfaction (figure rating scale), suicidal thoughts and behaviors (ideation, planning and attempts), and had body weight and height measured to calculate the body mass index (BMI = body weight divided by squared height). Binary logistic regression was used to data analysis. Results: Greater prevalence of ideation, planning and suicidal attempts was found among female than male. Adolescents who were dissatisfied by thinness and by overweight were more likely to ideation and planning suicide. No associations between suicidal attempts and body image dissatisfaction were found. Conclusions: Females had higher prevalence of ideation, planning and attempt than males. Regardless of sex, age, BMI and sexual maturation, the adolescents who were dissatisfied with their body (both by thinness and by overweight) were more likely to ideation and planning the suicide, compared to those who were satisfied. Giving that these adolescents are in school age, the school can be an agent of discussion on the subject, assisting to prevent body dissatisfaction and suicidal outcomes. Other professionals who work with adolescents and relatives need to pay attention to these issues.